Using the Context, Input, Process and Product (CIPP) Model in the Evaluation of Training Programs - Khalif Ashhabul Umam; Iip Saripah (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2018)
Evaluation of training program is made to establish the achievement of program objectives and to provide recommendations for program improvements. In this article, use of the CIPP (Context, Input, Process, and Product) evaluation model in training programs is discussed. It is an evaluation research, with a descriptive quantitative approach involving 16 training program participants as research subjects. The data collection techniques were based on questionnaires as the main instrument, with interview guides and observation guidelines as supporting instruments. The data analysis was made by comparing the scores obtained with the ideal score and multiplying by 100%; the results of these calculations were then grouped into a number of criteria that had been established. The results of the study indicate that the context dimension consisting of training objectives, training needs assessment, and state agency program organizers obtained a PE (Percentage of Effectiveness) score of 75.04%, placing it in the